대장암 환자의 옥살리플라틴(oxaliplatin) 유도 말초신경병증에 대한 약물유전학적 접근: 체계적 문헌고찰 - 안수정; 최소영; 정혜정; 추상희 (Journal of Korean biological nursing science, 2018)
Purpose: Peripheral neuropathy is common among colorectal cancer (CRC) patients who undergo oxaliplatin-based (OXL) chemotherapy. A pharmacogenetic approach can be used to identify patients at high-risk of developing severe neuropathy. This type of approach can also help clinicians determine the best treatment option and prevent severe neurotoxicity. The purpose of this study is to investigate the evidence of pharmacogenetic markers for OXL-induced peripheral neuropathy (OXIPN) in patients with CRC. Methods: A systematic literature search was conducted using the following databases up to December 2017: Pubmed, EMBASE, and CINAHL. We reviewed the genetic risk factors for OXIPN in observational studies and randomized controlled clinical trials (RCTs). All processes were performed independently by two reviewers. Results: Sixteen studies published in English between 2006 and 2017 were included in this review. A genome-wide association approach was used in one study and various candidate genes were tested, based on their functions (e.g., DNA damage or repair, ion channels, anti-oxidants, and nerve growth etc.). The genes associated with incidence or severity of OXIPN were ABCG2, GSTP1, XRCC1, TAC1, and ERCC1. Conclusion: This study highlighted the need and the importance of conducting pharmacogenetic studies to generate evidence of personalized OXIPN symptoms management. Additional studies are warranted to accelerate the tailored interventions used for OXIPN in patients with CRC (NRF-2014R1A1A3054386).